An Analysis of 20 Cases of Parasagittal and Falcine Meningioma: Our Institutional Experience - Boopalan Sakthisrinivasan; Rajamani Veerapandian; Ramiah Manimaran (Journal of Pharmacy and Bioallied Sciences)
Parasagittal and falcine meningiomas pose significant challenges to surgical removal due to their close proximity to the superior sagittal sinus and venous structures, posing high complications. The study evaluated the effectiveness of a microsurgical approach in reducing complication rates and achieving good tumor control in parasagittal and falcine meningiomas. A study involving 20 patients with parasagittal and falcine meningiomas underwent surgery at Madurai Medical College between January 2023 and December 2023. Preoperative imaging and meticulous planning were used to preserve critical venous structures and maximize safe tumor resection. Outcomes were assessed on complete resection rates, postoperative complications, and overall survival. Complete resection was achieved in 75% of cases, with a postoperative morbidity rate of 25%. Patients with tumors involving the middle third of the superior sagittal sinus faced higher risks of postoperative complications, emphasizing the importance of precise surgical navigation. The study found that a microsurgical approach, coupled with comprehensive preoperative assessment, significantly improved patient outcomes, reducing complications and enhancing survival rates. The study emphasizes the significance of a multidisciplinary approach in managing parasagittal and falcine meningiomas, emphasizing the need for advanced imaging techniques and microsurgical planning.